Financial Management Challenges for the Board of Directors in Joint-Stock Companies: An Analytical Study in Light of the New Saudi Companies Law and Corporate Governance Regulations - Maysoun bint Abdulwahab bin Hamid Al-Mohammadi (International Journal of Law Research and Studies, 2025)
This study examines the financial management challenges encountered by boards of directors in joint-stock companies under the Saudi Companies Law and the Corporate Governance Regulations. It approaches these challenges through three principal areas of analysis. The first area, titled “Issues Related to the Misuse of Company Funds,” addresses several practices that constitute improper use of corporate assets, including non-compliance with profit distribution rules, the overvaluation of in-kind contributions, the granting of loans to board members in contravention of statutory provisions, and the exploitation of company funds for personal purposes. The second area, titled “Issues Related to Disclosure, Transparency, and Abuse of Power,” explores various forms of misconduct, such as the submission of false or misleading information in company reports and financial statements, the misuse of insider information, the acceptance of benefits or advantages from third parties, and the concealment of the company’s actual financial position. The study seeks to identify and examine the most significant financial management issues facing boards of directors in joint-stock companies, assess their impact on corporate stability, and highlight the preventive role that corporate governance can play in reducing and mitigating such issues. The study adopts an analytical methodology. Among its key findings, the study concludes that the misuse of insider information and the provision of false or misleading data in financial reports and the company’s balance sheet are among the most detrimental issues affecting directors’ compliance with their duties of disclosure, transparency, and the avoidance of conflicts of interest or personal gain. The study further finds that the effective implementation of corporate governance principles helps ensure the lawfulness and soundness of the decisions and actions taken by board members. In light of these conclusions, the study recommends that the Saudi regulator provide more detailed guidance on the types of information that fall within the scope of falsification and misleading disclosure in financial statements and reports—referred to in Article 260(a) of the Companies Law—while excluding information that reflects accounting estimates that cannot be calculated with precision or unintentional errors that do not amount to material misstatements.
Keywords: Joint-Stock Company; Board of Directors; Corporate Governance; Financial Management; Disclosure; Transparency; Abuse of Power